The Reflection of Hemingway’s Life as a Writer through Harry’s Characters in the Short Story “The Snows of Kilimanjaro” - Kawentar, Rukma (LANTERN (Journal on English Language, Culture and Literature), 2014)
The writer would like to analyze short story “The Snows of Kilimanjaro” by Ernest Hemingway. The purpose of this study is to know the similarities and differences between Harry and Hemingway’s life. By using theory will to meaning by Viktor Frankl and expressive approach, the writer will prove the similarities and differences in their life. In addition, the writer also analyzes the setting and symbols in the story to support the psychological analysis. The result of this research shows not only there are many similarities of Hemingway’s life reflected in this short story but also many differences that indicates these differences is latent desires of Hemingway.